Masjids in the Prophet’s time and now: what has gone wrong? - Hasan, Md. Mahmudul (2020)
In order to bring back the educational role of masjids, the imams and khatibs need to be more knowledgeable about various aspects of Islamic teachings. They should also know about other religious traditions as well as secular worldviews. They must be better trained in educating the community and interpreting Islam for a contemporary setting. Their job scope needs to re-examined and redefined. Friday khutbahs in masjids should be tailored to meet the requirements of the community and their contents, updated on a regular basis in response to various developments in society. Khutbahs must touch on current debates and discuss problems and challenges facing Muslim society and the world at large. Topics of khutbahs must be more relevant to contemporary developments and needs, which merits a separate study and further discussion and elaboration.